THE EFFECT OF NIGELLA SATIVA CRUD EXTRACTS ON MICROORGANISMSISOLATED FROM CLINICAL INFECTIONS. - عبد الصاحب رياض; عزيز غازي; المُلا حواء (Iraqi Journal of Science, 2024)
Crud extracts of N. sativa seeds were prepared :Oil extract using soxhelt (OS), Oil extract using Reflux(OR),ethanol extract (EE), aqueous extract (AE )and buffer extract (BE).The chemical tests indicated that N. sativa seeds have the active compounds include, alkaloids , tannins , glycosides, resins, saponins, coumorins and flavonoids The antimicrobial activity against 50 isolates (40 clinical isolates, 7 isolates from hospitals contamination and 3 standard strains )were studied by using disk diffusion and wells methods, the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were determined by using agar dilution method . The results revealed that the most efficienty extracts were OR ,followed by OS , EE, AE and the less efficienty extracts was BE.The most sensitive microorganisms to the extracts ( decreased MIC and MBC values ) were gram positive bacteria ( S. aureus, B. cereus, B. subtilis, S. epidermidis and S. fecales) while gram negative bacteria appears less sensitive (P. aeroginosa was the most sensitive, followed by E. coli but K. pneumoniae , P. mirabilis and S. marcesens didn’t show any response to all extracts), C.albicans revealed more sensitive than A. niger